Treatment of children with mobile flat feet with modified Kidner operation - Ergashov Maftun Muxitdinovich (Zien Journals, 2024)
In this article, a new modified Kidner's operation is used to treat flat feet, a common disease in children, so that children with flat feet can get up early without complications and get rid of flat feet so that children can walk on healthy feet.
Keywords: Kidner's operation; modified Kidner's operation; mobile flat foot; posterior tiabial tibial tendom disfunction